2016
DOI: 10.1016/j.jff.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of green tea polyphenols on development and reproduction in Drosophila melanogaster

Abstract: Although, green tea has numerous health benefits, adverse effects with excessive consumption have been reported. Using Drosophila melanogaster, a decrease in male fertility with green tea was evidenced. Here, the extent of green tea toxicity on development and reproduction was investigated. Drosophila melanogaster embryos and larvae were exposed to various doses of green tea polyphenols (GTP). Larvae exposed to 10 mg/mL GTP were slower to develop, emerged smaller, and exhibited a dramatic decline in the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
(72 reference statements)
7
19
2
Order By: Relevance
“…Consistent with previous results from studies conducted on other insects [ 29 – 31 ], C. sinensis extract exhibited larvicidal activity in addition to induction of growth disruption effects. However, in contrast to our dosage data, these studies reported relatively higher extract dosages of between 10 mg/ml to 75 mg/ml (translating to 10,000–75,000 ppm) to achieve similar larvicidal potency.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous results from studies conducted on other insects [ 29 – 31 ], C. sinensis extract exhibited larvicidal activity in addition to induction of growth disruption effects. However, in contrast to our dosage data, these studies reported relatively higher extract dosages of between 10 mg/ml to 75 mg/ml (translating to 10,000–75,000 ppm) to achieve similar larvicidal potency.…”
Section: Discussionsupporting
confidence: 91%
“…albopictus and Culex quinquefasciatus [ 29 , 30 ]. Further, green tea polyphenols have been shown to cause deleterious effects on the development and reproduction fitness of D. melanogaster [ 31 ]. Therefore, we designed a study to evaluate the efficacy of green tea leaf extract and its constituents against immature larval stages of A. arabiensis and A. gambiae ( s.s .).…”
Section: Introductionmentioning
confidence: 99%
“…Green tea has high polyphenolic content with known iron‐binding properties (Khokhar & Apenten, ; Perron & Brumaghim, ). We investigated the ability of a green tea polyphenol extract, consisting of ∼80% catechin content (Lopez et al., ), to modulate total body iron levels. We found a 39% decrease (245.9 ± 24.9 vs. 403.6 ± 29.4 nmol Fe/mg protein) in total body iron compared to controls ( P = 0.003, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that green tea increased the lifespan of w 1118 male Drosophila by 19% while reducing fertility (Lopez et al., ). We further identified negative impairments in the reproductive organs of Drosophila treated with green tea, including atrophied testes in male flies (Lopez et al., ). In consideration of the inverse relationship between reproduction and lifespan in Drosophila , a well‐documented occurrence (Flatt, ; Kirkwood & Rose, ; Prowse & Partridge, ), and the importance of iron for spermatogenesis (Hales, ; Metzendorf & Lind, ; Tvrda, Peer, Sikka, & Agarwal, ), we questioned whether green tea acts by modulating iron regulation to affect lifespan and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Later, they reported that GTPs in high dose (10 mg/ml) declined the rate of development and the number of emerged offspring in D. melanogaster larvae. Besides, reproductive ability and survival decreased in female offspring, but not in males (Lopez et al, ).…”
Section: Mutagenicity Genotoxicity Carcinogenicity and Developmentmentioning
confidence: 99%